COMPARATIVE ANALYSIS OF THE LEVEL OF HIV RNA IN CEREBROSPINAL FLUID AND PLASMA IN HIV-ASSOCIATED NEUROLOGICAL DISEASES - Lуtvуn K.Yu.; Shostakovych-Koretska, L.R.; Hubar, I.O. (World of Medicine and Biology, 2018)
Summary. HIV is present in the central nervous system, starting with primary viremia and, in the absence of treatment, throughout the infection. HIV RNA level in cerebral spinal fluid (CSF) is considered to be an important marker of neurological diseases of the central nervous system in HIV-infected patients. The purpose of the study is to determine the HIV RNA level in the cerebrospinal fluid and plasma in HIV-associated infectious neurological diseases, depending on the immunological status, the etiology and the consequences of the disease. Materials and methods. Data were analyzed for 48 patients aged 21 to 54 years with HIV infection and the presence of infectious diseases of the central nervous system (CNS), including: cerebral tuberculosis - 15 (31.3%), fungal infections (candidiasis, cryptococcosis) - 6 (12.5% ), encephalitis caused by viruses: the Epstein-Barr virus (EBV), cytomegalovirus (CMV), herpes simplex virus (HSV) - 11 (22.9%), encephalitis of unspecified etiology - 9 (18.7%), cerebral toxoplasmosis - 7( 14.6%) cases. The majority of patients - 29 (60.4%) were discharged from a hospital with improvement in condition, and 19 (39.6%) patients with severe illness died due to CNS disease. The determination of HIV RNA in CSF was carried out using a polymerase chain reaction based on standardized technology. Statistical processing of the results of the study was conducted using the programs Statistica v.6.1® and MedCalс v.11.5.0 (free download). In order to determine the discriminatory significance of levels of viral load of HIV RNA to predict the course of neurological disease, ROC analysis was performed. Results and discussion. A higher HIV RNA viral load was observed in dead patients - 5.14 (4.39-5.99) Lg copies/ml in CSF and 5.60 (5.25 - 5.99) Lg copies/ml in plasma, which was reliably higher than the one of those who were discharged with improvement status - 4.31 (3.0 - 5.06) Lg copies/ml and 5.10 (3.85-5.83) Lg copies/ml respectively (p